A calculation method of transmission line equivalent geometrical parameters based on power-frequency parameters. (October 2019) - Li, Botong; Lv, Mingrui
Highlights: The effect of frequency-dependent line parameters should be considered in the researches. The equivalent geometrical parameters of transmission line are calculated by power-frequency parameters. The frequency-dependent line parameters are obtained by power-frequency parameters. Abstract: The geometrical parameters of the transmission line are prerequisite for precisely calculating frequency-dependent parameters as well as studying the electromagnetic transient process. Considering that the equivalent geometrical parameters are difficult to obtain directly, this paper proposes a method to calculate geometrical parameters of overhead transmission line using impedance and capacitance matrices measured at power frequency. By applying the inverse derivation of the Carson formula, the expressions of the average height of the line and the conductor radius can be obtained if the self-impedance of the line is known, while the distance between two conductors and that between one conductor and the image of another can be found with the mutual impedance. On this basis, if both the impedance and capacitance of the transmission line at power frequency are given, iteration can be used for higher accuracy. Finally, MATLAB- and PSCAD/EMTDC-based simulations are carried out verifying the effectiveness and sensitivity of the method.